The Effect of Sustainability Report Disclosure on Stock Prices: An Educational Review - Maulidya, Putri; Azis, Mohammad Taufik; Djajuli, Mohamad (CV. Tripe Konsultan, 2025)
This study aimed to examine the effect of sustainability performance disclosure on stock prices in mining sector companies listed on the Indonesia Stock Exchange. The disclosure is assessed through three dimensions: economic, social, and environmental performance, based on the Global Reporting Initiative (GRI) standards. Using multiple linear regression analysis with secondary data from sustainability reports and stock price data, the study evaluates both partial and simultaneous effects of the independent variables. The results show that environmental performance disclosure has a significant negative influence on stock prices, social performance has a weak and marginally significant effect, while economic performance disclosure has no significant impact. However, the overall model is statistically significant, indicating that the combined disclosure of the three dimensions has a strong influence on stock price movements. The coefficient of determination (R²) indicates that 95.85% of stock price variation is explained by the model, highlighting a high explanatory power. From an educational review perspective, the findings emphasize the importance of integrating sustainability reporting into business and financial education curricula. By understanding how environmental, social, and economic disclosures affect investor perceptions and market behavior, students, policymakers, and corporate stakeholders can gain deeper insights into the practical relevance of sustainability in capital markets. This educational lens highlights the need for future leaders to balance short-term financial performance with long-term sustainability goals. The study therefore recommends that companies enhance the quality and transparency of sustainability reporting, especially in environmental aspects, to better align with long-term investor expectations and strategic corporate value creation.